Online Gambling, Maintenance Neglect, and Marital Breakdown: A Maqasid al-Shariah Analysis of Islamic Court Decision Number. 304/Pdt.G/2025/PA.SJJ - Desminar Desminar; Mursal Mursal; Romi Saputra; Sri Wedari (Program Pascasarjana IAIN Langsa, 2026)
The rise of online gambling in the digital era has created new challenges to household stability, particularly when it causes the neglect of alimony obligations within marriage. This study aims to analyze the divorce decision in Case Number 304/Pdt.G/2025/PA.SJJ by examining the relationship between alimony neglect, online gambling, and marital breakdown from normative legal and maqasid al-shariah perspectives. This research employs a qualitative case study approach using primary data obtained through interviews with the plaintiff, defendant, presiding judge, and an Islamic law scholar. Secondary data were collected from court decisions, statutory regulations, and relevant literature. Data were analyzed using the Miles and Huberman interactive model combined with case interpretation. The findings show that online gambling became a catalyst for the misuse of household financial resources, resulting in neglected alimony obligations and prolonged domestic conflict. Normatively, these conditions fulfill the legal grounds for divorce under Law Number 1 of 1974 and Kompilasi Hukum Islam (KHI). From the maqasid al-shariah perspective, such behavior violates the protection of life (hifz al-nafs), property (hifz al-mal), intellect (hifz al-aql), and offspring (hifz al-nasl). Therefore, the court's decision reflects the principle of preventing greater harm within the household. Consequently, the study contributes to the development of maqasid-based legal interpretation in contemporary divorce cases, particularly those arising from emerging digital social problems such as online gambling.